Analogical Asides on Case-Based Reasoning - Keane, Mark T. (Trinity College Dublin, Department of Computer Science, 1994)
This paper explores some of the similarities and differences between cognitive models of analogy and case-based reasoning systems. I first point out a paradox in the treatment of adaptation in analogy and in case-based reasoning; a paradox which can be only resolved by expanding the role of adaptation in cognitive models of analogy. Some psychological research on the process of adaptation in human subjects is reported and then the implications of this research are propagated into analogy and then on into CBR. The argument is that some of the existing stages in CBR should be integrated into a more stream-lined architecture that would be more efficient than current schemes.
Also in Wess, S., Althoff, K-D., & Richter, M.M. (Eds.), Topics in Case-Based Reasoning. Amsterdam: Springer-Verlag.
Keywords: Computer Science